Hormone-mediated neural remodeling orchestrates parenting onset during pregnancy - Ammari, Rachida; Monaca, Francesco; Cao, Mingran; Nassar, Estelle; Wai, Patty; Del Grosso, Nicholas A; Lee, Matthew; Borak, Neven; Schneider-Luftman, Deborah; Kohl, Johannes (Science (American Association for the Advancement of Science), 2023)
During pregnancy, physiological adaptations prepare the female body for the challenges of motherhood. Becoming a parent also requires behavioral adaptations. Such adaptations can occur as early as during pregnancy, but how pregnancy hormones remodel parenting circuits to instruct preparatory behavioral changes remains unknown. We found that action of estradiol and progesterone on galanin (Gal)-expressing neurons in the mouse medial preoptic area (MPOA) is critical for pregnancy-induced parental behavior. Whereas estradiol silences MPOA neurons and paradoxically increases their excitability, progesterone permanently rewires this circuit node by promoting dendritic spine formation and recruitment of excitatory synaptic inputs. This MPOA -specific neural remodeling sparsens population activity in vivo and results in persistently stronger, more selective responses to pup stimuli. Pregnancy hormones thus remodel parenting circuits in anticipation of future behavioral need.